The Chilean Case and the Latin American Pink Tide: Between Democracy and Developmentalism (Alternautas, 2016)
The so called Marea Rosada (Pink Tide) specifically refers to the turn that several Latin American governments took by the end of the 90s, in favor of public and social agendas that opposed the neoliberal order that characterized the region in the previous decades. These new agendas also broke away from the age-old ideal of revolutionary partisanship, pursuing a critique of neoliberalism that was not reducible to a radical (impossible) delinking still embedded in the logic of accumulation. The new political agenda brought to the fore by the governments of the Marea Rosada without opposing neoliberalism tried to radically modify its logic and produce a more humane economy. In spite of the anti-imperialist and nationalist rhetoric that have flourished in the regional Left, it is also true that for cases such as the Chilean and the Brazilian ones the scene is dominated by a type of government that seeks to correct unjust income distribution while maintaining a disciplined fiscal budget as to facilitate its entry into international markets.